Pengaruh Beberapa Jenis Praperlakuan Terhadap Peningkatan Rendemen Hidrodistilasi Minyak Atsiri Gaharu - Hendri Aldrat; Khoerunnisa; Karina Wandani; Supandi; M. Yanis Musdja (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Agarwood essential oil (minyak atsiri gaharu or minyak gaharu) has the potential to be developed as aromatherapy to help reduce stress, but its availability in nature is not abundant, so effective efforts are needed to get optimal results. Although various pretreatments before hydrodistillation are known to enhance the yield of agarwood oil, no comparative study using the same sample has been reported to date. This research aims to compare the yield and profile of agarwood oil compounds obtained from maceration, microwave, ultrasonic and fermentation using ragi tapai and ragi tempe pretreatments. The research was carried out by pretreatment extraction, distillation of agarwood powder, identification of essential oil compounds via Gas Chromatography Mass Spectrometry (GC-MS), and hedonic tests. The distillation results showed that pretreatment yeast tapai fermentation had the highest percentage yield of agarwood oil at 0.050% followed by Fusarium sp fermentation. (0.036%), ultrasonic (0.034%), microwave (0.030%), maceration (0.024%), control (0.018%) and ragi tempe (0.002%). Six compounds were consistently found in each sample, such as α-agarofuran, neoisolongifolene, α-santalol, δ-guaiene, dihydrocolumellarin, and hexadecanoic acid. The most sesquiterpene compounds were obtained from pretreatment using tempeh yeast. Based on the research results, it is known that maceration, microwave, ultrasonic and fermentation pretreatments can increase the yield and influence the compound profile of agarwood oil.